4(-3x)=y F f f f f f f f d d d d d d d d d d d d d d d d d d d d d d
f(0)=64, f(1)=66, f(2)=72, f(3)=82, f(4)=96,...=2,6,10,14,...=2{1,3,5,7,...}
This can be written 2{2x+1}, so the intervals on which f(x) increases are 4x+2.
F(x) = (x + 3)²
g(x) = f(x) - 7.
g(x) = (x + 3)² - 7
g(x) = (x + 3)(x + 3) - 7
g(x) = x*x + x*3 +3*x + 3*3 - 7
g(x) = x² + 3x + 3x + 9 - 7
g(x) = x² + 6x + 2
Answer:
The error is in step 3. You cannot use a property of logarithms to prove that same property.
Step-by-step explanation:
Here we the proof of the quotient rule as
If Logₐx = M and Logₐy = N
Then x = and y =
x ÷ y = ÷ =
Take log of both sides we get
Logₐ(x÷y) = Logₐ
Logₐ(x÷y) =M-N logₐa
Logₐ(x÷y) =M-N
∴Logₐ(x÷y) = Logₐx - Logₐy